Fish Meal Replacement and Early Mild Stress Improve Stress Responsiveness and Survival of Fish after Acute Stress - Zare, Mahyar; Kazempour, Mohammad; Hosseini, Hossein; Hosseini Choupani, Seyedeh Mahsa; Akhavan, Sobhan R; Rombenso, Artur; Esmaeili, Noah (Animals, 2023)
Stress responsiveness and fish meal (FM) replacement are two of the most important concerns toward achieving sustainable aquaculture. The purpose of this study was to see how early mild stress (netting) and FM replacement with meat and bone meal (MBM) affected oscar (Astronotus ocellatus; 5.2 ± 0.9 g) growth, hematology, blood biochemistry, immune responses, antioxidant system, liver enzymes, and stress responses. Oscars were subjected to a 3 × 3 experimental design (three fish meal replacement levels: 250, 180 and 110 g/kg of FM in diets; three stress periods: 0-, 2- and 3-times early mild stress). After ten weeks of the experiment, FM levels in diets did not affect growth data, but the survival rate after the acute confinement (AC) stress was lower in 11FM treatments (47.7% compared to 67.7%) than others. Fish exposed to the 3Stress schedule had a lower growth (31.03 ± 6.50 g) and survival rate (55.5%) after the AC stress than the 2Stress group (38.92 ± 6.82 g and 70.0%). Lower survival and growth rate in the 3Stress and 11FM groups coincided with the lowest blood performance, total protein, lysozyme, complement C4, complement C3, immunoglobulin, superoxide dismutase, catalase, glutathione peroxidase, and the highest glucose, cortisol, low-density lipoprotein and aspartate aminotransferase serum levels. Altogether, this study revealed that it is possible to replace FM with MBM up to 28% (180 g/kg of FM) without negative effects on the growth and health of juvenile oscar as dietary 110 g/kg of FM impaired fish health. While fish welfare should be considered, we can conclude that mild stress (2Stress) during the farming period, but without adding excessive alternative protein sources, can improve the stress responsiveness of oscar.
Keywords: stress responses; blood performance; antioxidant responses; blood biochemistry; stress physiology